Anisotropie damage applied to numerical ductile rupture - Croix, Patrick; Lauro, Franck; Oudin, Jérôme; Christlein, Jens (European Journal of Computational Mechanics, 2001)
Damage models models are applied for elasto-viscoplastic materials. They take microvoids volume fraction evolution into account by means of the growth, the nucleation and coalescence of microvoids. The anisotropy of the material is introduced with the Hill's potential in the modified yield function. The anisotropy of the damage is taken into account in one mode! with the shape of the microvoids. The void is defined as an el! ipso id which could evolve in shape and direction according to the loading direction and the geometry of the structure. These models are applied on unit cel! specimens and on a double nonaxisymmetrical V-notched specimen. The influence of the microvoids shape and their orientations on the final ductile rupture is shawn.